A classroom observation tool for scaffolding reading comprehension. (April 2017) - Smit, Nienke; van de Grift, Wim; de Bot, Kees; Jansen, Ellen
Abstract: An important goal of educational research is to find out which teaching practices are effective in promoting students' learning. In order to assess these practices, adequate observation instruments are needed. Existing observation schemes for language teaching are not suitable to gauge which teaching strategies scaffold EFL reading comprehension in particular and language learning in general. Therefore, we developed a new instrument: the English Reading Comprehension Observation Protocol. The focus of the instrument is on the role of the EFL teacher who helps students to move from learning to read to reading to learn in English. We conducted a generalizability study in order to establish the instrument's reliability. Twenty lessons taught by five experienced teachers were recorded and observed by five experienced teacher educators. The results of the generalizability study, in which we disentangled sources of variance, show that a large proportion of the variance can be attributed to differences between the teachers. This shows that the instrument has a high reliability and can help teachers identify their strengths and room for development. The instrument takes the form of a checklist and is easy to use for professional development purposes.